Two tripartite classification systems of CD86+ and CD206+ macrophages are significantly associated with tumor recurrence in stage II-III colorectal cancer - Xu, Guozeng; Mo, Yuzhen; Li, Jing; Wei, Qingqing; Zhou, Fuxiang; Chen, Jian (Frontiers in Immunology, 2023)
The prognostic value of tumor-associated macrophages remains unclear in colorectal cancer (CRC). Two tripartite classification systems, namely, ratio and quantity subgroups, were investigated as the prognostic stratification tools for stage II-III CRC. We assessed the infiltration intensity of CD86+ and CD206+ macrophages in 449 cases with stage II-III disease by immunohistochemical staining. Ratio subgroups were defined by the lower- and upper-quartile points of CD206+/(CD86++CD206+) macrophage ratio, including the low-, moderate-, and high-ratio subgroups. Quantity subgroups were defined by the median points of CD86+ and CD206+ macrophages and included the low-, moderate-, and high-risk subgroups. The main analysis was recurrence-free survival (RFS) and overall survival (OS). Ratio subgroups (RFS/OS: HR=2.677/2.708, all p<0.001) and quantity subgroups (RFS/OS: HR=3.137/3.250, all p<0.001) could serve as independent prognostic indicators that effectively predicted survival outcomes. More importantly, log-rank test revealed that patients in the high-ratio (RFS/OS: HR=2.950/3.151, all p<0.001) or high-risk (RFS/OS: HR=3.453/3.711, all p<0.001) subgroup exhibited decreased survival outcomes after adjuvant chemotherapy. The predictive accuracy of the quantity subgroups within 48 months was higher than that of the ratio subgroups and tumor stage (all p<0.05). Ratio and quantity subgroups could serve as independent prognostic indicators that could potentially be incorporated into the tumor staging algorithm to improve prognostic stratification and provide better predictions of survival outcomes in stage II-III CRC after adjuvant chemotherapy.